2018
DOI: 10.1089/jmf.2017.0071
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Korean Ginseng, GINST15, on Hypo-Pituitary-Adrenal and Oxidative Activity Induced by Intense Work Stress

Abstract: The effect of GINST15, an enzyme fermented ginseng supplement, on hormonal and inflammatory responses to physical stress in humans is unknown. The purpose of this investigation was to examine the constitutive and stress-induced effects of GINST15 supplement on hypo-pituitary-adrenal (HPA) and antioxidant activity in addition to muscle damage. Ten women (age: 38.7 ± 7.8 years; height: 163.81 ± 4.4 cm; body mass 76.0 ± 11.6 kg) and nine men (age: 41.2. ± 9.7 years; height: 177.4 ± 5.3 cm; body mass: 88.5 ± 5.0 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 65 publications
0
19
1
1
Order By: Relevance
“…A combination of psychological and physical stress could induce chronic inflammation and subsequent disease [ 23 ]. For such reasons, a dietary regimen including antioxidants was suggested [ 24 , 25 ], but it is not clear if such a strategy is of much help [ 26 ], especially if the working conditions otherwise remain unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of psychological and physical stress could induce chronic inflammation and subsequent disease [ 23 ]. For such reasons, a dietary regimen including antioxidants was suggested [ 24 , 25 ], but it is not clear if such a strategy is of much help [ 26 ], especially if the working conditions otherwise remain unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…They found that, in response to severe exercise, CK supplementation resulted in dose-dependent declines in circulating cortisol and augmented antioxidant activity. This study first provided insights into the impact of ginseng treatment on the reactions to the stress associated with work [ 118 ]. A recent continued study by the same research group demonstrated direct evidence on task-related brain activity by evaluating CK’s treatment on behavioral performance and electroencephalography measures of cortical activity.…”
Section: Health-promoting Activitiesmentioning
confidence: 99%
“…During upper-body CRTs, dose-dependent increases in P3b latency after exercise could indicate that a higher dose of CK impaired processing times related to the allocation of attentional resources (Polich, 2007;Kumar et al, 2010). Nevertheless, given the sensitivity of P3b to autonomic inputs (Nieuwenhuis et al, 2005) and CK-induced reductions in circulating cortical after exercise (Flanagan et al, 2018), relative increases in P3b latency may reflect reductions in exercise-induced sympathetic activity (Kubota et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The participants, supplementation regimen, and experimental approach are fully detailed elsewhere (Flanagan et al, 2018). A general overview with considerations specific to this study is provided here.…”
Section: Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation